CD44 Expression Predicts Prognosis of Ovarian Cancer Patients Through Promoting Epithelial-Mesenchymal Transition (EMT) by Regulating Snail, ZEB1, and Caveolin-1 - Zhou, Jiayi; Du, Yan; Lu, Yiling; Luan, Baoxin; Xu, Congjian; Yu, Yinhua; Zhao, Hongbo (Frontiers in Oncology, 2019)
Objectives: CD44, a transmembrane glycoprotein, is involved in the generation of a stem cell niche and maintaining stem cell quiescence. The aim of this study was to evaluate its contribution to ovarian cancer prognosis and progression, as well as explore the possible mechanisms. Materials and Methods: The expression of CD44 in tissue microarray of 90 ovarian cancer patients was detected by immunohistochemistry. Kaplan-Meier method and Cox proportional hazard model were used to evaluate the factors associated with 5-year overall survival and disease-free survival. CD44 was knocked down by small interfering RNA, the expression of Snail, ZEB1, and Caveolin-1 in a stable Snail-expressing ovarian cancer cell line HO8910PM-Snail (HOPM-Snail) and its control cell line HO8910PM-vector (HOPM) was detected by western blotting analysis. Cell clone formation, migration, and invasion of HOPM-Snail and HOPM cells with CD44 silencing were examined by 3-D culture assay, wound healing assay, and transwell assay, respectively. Results: Over-expression of CD44 was associated with advanced histological grade (p = 0.014) and FIGO stage (p = 0.001). Multivariate analysis showed that CD44 expression was an independent prognostic factor to predict both overall survival (p = 0.004) and disease-free survival (p = 0.025) of ovarian cancer patients. Down-regulation of CD44 expression by small silencing RNA abrogated both basal Snail expression and TGF-β1-induced Snail expression in HOPM and HOPM-Snail cells. In addition, CD44 knockdown caused a decrease in ZEB1 expression. RPPA data indicated that Caveolin-1 may be another regulative target of CD44, and western blotting analysis confirmed that CD44 knockdown caused an increase in Caveolin-1 expression. However, there was no noticeable reciprocal regulation among ZEB1, Caveolin-1, and Snail. Moreover, CD44 knockdown caused a decrease in cell clone formation, migration, and invasion of HOPM and HOPM-Snail cells. Conclusions: As both Snail and ZEB1 are crucial inducers of epithelial-to-mesenchymal transition (EMT), our data suggested that CD44 may be crucial for the EMT process of ovarian cancer. Therefore, CD44 may be a potential prognostic marker as well as treatment target for ovarian cancer.